Commercialised history : popular history magazines in Europe : approaches to a historico-cultural phenomenon as the basis for history teaching - Popp, Susanne; Schumann, Jutta; Hannig, Miriam (2014)
This volume of essays is the result of the EU project EHISTO, which dealt with the mediation of history in popular history magazines and explored how history in the commercialised mass media can be used in history teaching in order to develop the media literacy and the transcultural competences of young people. The volume offers articles which for the first time address the phenomenon of popular history magazines in Europe and their mediating strategies in a foundational way. The articles are intended as introductory material for teachers and student teachers. The topic also offers an innovati.